Routledge Handbook of Ecocultural Identity (Taylor & Francis, 2025)
The Routledge Handbook of Ecocultural Identity brings the ecological turn to sociocultural understandings of self. The editors introduce a broad, insightful assembly of original theory and research on planetary positionalities in flux in the Anthropocene – or what in this Handbook cultural ecologist David Abram presciently renames the Humilocene, a new “epoch of humility.” Forty international authors craft a kaleidoscopic lens, focusing on the following key interdisciplinary inquiries: